Monitoring and assessing the influence of social, economic and policy factors on sustainable land management in drylands - Nkonya, Ephraim M.; Winslow, M.; Reed, M. S.; Mortimore, M.; Mirzabaev, A. (Wiley, 2011)
Socio‐economic and policy dynamics strongly influence sustainable land management and consequently the capacity of land to sustain valuable ecosystem services, so it is important that they be incorporated into monitoring and assessment regimes aimed at combating desertification and land degradation. Systematic surveys can provide standardized information on socio‐economic and policy dynamics, supplemented by deeper cause–effect understanding emanating from case studies. Countries increasingly collect geo‐referenced socio‐economic data as part of regular censuses and surveys; the collection of information relevant to sustainable land management could be efficiently added to those exercises. Geographic information systems analysis and modeling can then link social, economic, and policy data with biophysical data to support decision‐making. The identification of typical socio‐economic and policy cause–effect patterns is a potential means for summarizing complex human–environmental interactions in more insightful ways. By integrating monitoring techniques based on both local and scientific knowledge, the relevance, accuracy, reliability, and sensitivity of monitoring can be improved. Such integration can also foster mutual commitment and effective joint planning and action between governments and land‐users leading to the implementation of effective sustainable land management practices. Copyright © 2010 John Wiley & Sons, Ltd.